Prelude to the 1979 Lancaster House Constitutional Conference on Rhodesia: The Role of International Economic Sanctions Reconsidered (Historia, 2021)
EnglishThis article re-examines the role of international economic sanctions in helping to resolve the Rhodesian political impasse. This situation was the result of the white minority Rhodesian government’s unilateral declaration of independence (UDI) from Britain in November 1965. The Rhodesian case is studied in the light of the debate on the efficacy or ineffectiveness of sanctions as a weapon of international diplomacy. It is argued that, while sanctions were neither the only nor the most important factor in bringing the Rhodesian government to a negotiated political settlement at Lancaster House in 1979, they were, nevertheless, a very significant factor that worked, in tandem with other factors such as the escalating guerrilla insurgency and mounting international pressure. As a result of this combination of factors, the Rhodesian crisis was brought to an end and Zimbabwe’s independence was ushered in in 1980. During the initial period, sanctions appeared to be ineffective, as the Rhodesian economy appeared to enjoy prosperity in the period following their imposition. This led some commentators to dismiss sanctions as having failed to achieve the objectives of those who imposed them. It is however argued here that sanctions eventually succeeded in hamstringing the Rhodesian economy and in impairing the country’s ability to deal with the mounting guerrilla insurgency. Ultimately, it made it difficult for the Rhodesian government to continue ignoring world opinion, as well as the call for African majority rule. Thus, it is contended that sanctions did work in the Rhodesian case, even though they took much longer to bring the Rhodesian government down than had been anticipated.   AfrikaansAanloop tot die 1979 Lancaster House Grondwetlike Konferensie oor Rhodesië: ’n Herbesinning oor die Rol van Internasionale Ekonomiese Sanksies Hierdie artikel herevalueer die rol van internasionale ekonomiese sanksies in die ontknoping van die Rhodesiese politieke dooiepunt. Laasgenoemde het gevolg op die Rhodesiese wit minderheidsregering se eensydige onafhanklikheidsverklaring van Brittanje in November 1965. Die studie vind plaas in die lig van die debat oor die geslaagdheid, al dan nie, van sanksies as ’n wapen van internasionale diplomasie, veral in die geval van Rhodesië. Daar word geargumenteer dat, terwyl sanksies nie die enigste of selfs die belangrikste faktor was wat die Rhodesiese regering in 1979 tot ’n onderhandelde politieke skikking by Lancaster House gebring het nie, dit nogtans ’n uiters betekenisvolle faktor was wat in tandem met ander faktore gewerk het. Hierdie faktore sluit die groeiende guerrilla-insurgensie en stygende vlak van internasionale druk om die Rhodesiese krisis te beëindig, in en het Zimbabwe se onafhanklikheid in 1980 bewerkstellig. Aanvanklik het dit voorgekom asof die sanksies oneffektief was, gesien teen die skynbare voorspoed wat die Rhodesiese ekonomie geniet het in die periode wat op die instelling daarvan gevolg het. Dit het sommige kommentators daartoe gelei om sanksies as ’n mislukking af te maak. Hier word egter geargumenteer dat sanksies uiteindelik wel daarin geslaag het om die Rhodesiese ekonomie te kniehalter en teenstand teen die toenemende guerrillainsurgensie te bemoeilik. Hierdie faktore het dit uiteindelik vir die Rhodesiese regering moeilik gemaak om die wêreld se oproep om ’n Afrika meerderheidsregering langer te ignoreer. Daar word dus beweer dat sanksies wél in Rhodesië se geval gewerk het, selfs al het dit veel langer geneem om die Rhodesiese regering tot ’n val te bring, as wat aanvanklik voorsien is.
Keywords: Guerrilla insurgency; import substitution industrialisation (ISI); Lancaster House; majority rule; Rhodesia; Rhodesia Front Party; sanctions; Unilateral Declaration of Independence (UDI); Zimbabwe African National Union (ZANU); Zimbabwe African People’s Union (ZAPU); Guerrilla-insurgensie; invoer substituut industrialisasie (ISI); meerderheidsregering; Rhodesië; sanksies